Long-term trajectories of crime in the United Kingdom, 1982-2013 - Jennings, Will (UK Data Service, 2016)
The project for which this data was collated sought to explore the ways in which changes in economic and social policies resulted in changes in patterns of crime, victimisation and anxieties about crime and how shifts in social values affected national-level experiences and beliefs about crime and appropriate responses to it (such as support for punitive punishments like the death penalty). The researchers explored the long-term consequences of almost two decades (1979-1997) of neo-conservative and neo-liberal social and economic policies for the UK’s criminal justice system and the general experience of crime amongst its citizens. Using the Thatcher and Major governments (1979-1997) as the case study, the research team explored the experiences of crime, victimisation and fear of crime at the national and regional levels, and for key socio-demographic groups, since the 1970s (and where possible earlier than this). In order to complete these analyses repeated cross-sectional surveys of citizens in the UK were collated in such a way that the data could be analysed using techniques associated with time series and age-period-cohort analyses (as well as more conventional techniques). The surveys collated were the British Crime Survey (now called the Crime Survey for England and Wales), the British Social Attitudes Survey and the British Election Study. These survey series are also available from the UK Data Service.